Pengaruh Pembelajaran Cooperative Two Stay Two Stray Terhadap Hasil Belajar PKn Kelas V SD - Utami, Tika Agri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThis research was supported that the students tend to be passive. Because the teachers did not use the cooperative learning model. Cooperative learning model: two stay two stray of the learning model that can be used by the teachers solve the problem. This research was undertaken as an attempt to assess the effect of cooperative learning model:Two Stay Two Stray on the fifth grade student’s learning outcomes in Civic Education at SD Negeri 31 Pasir Kandang. This research adopted a quasy-eksperimental research design with quantitative approach. The population of this research was the fifth grade students at SDN 31 Pasir Kandang consisted of 58 students. The sample used in this research probability random sampling. The instrument for data collection was the written test consisted of 30 questions. The type of the data in this research was a primary data and the source of the data were the student’s learning outcomes by using t-test. Based on the calculation of t-test, t-count (2,1700) scored higher than t-table (2,00479) for alpha 0,05. The result obtained from the data showed that there is more positive effect of using cooperative learning model:two stay two stray toward fifth grade student’s learning outcomes in Civic Education at SDN 31 Pasir Kandang Kecamatan Koto Tangah Padang.           Keyword:Cooperative learning model:two stay two stray, learning outcomes